Animating Folktales: An Analysis of Animation Movies based on Folktales of three different Indian Languages - Maya Bhowmick (Litinfinite, 2020)
Folktales are the oldest and traditional means of communication having remained a powerful means of communication over the years. Since its inception this method of storytelling and communicating has changed its medium of transmission but not its manner of storytelling. For ages, oral tradition has been a medium of transmission of these stories and culture but with modernization, the medium changed to print, electronic, and now digital media. These folktales do not represent mere stories; but communicate the varied culture, tradition, rituals, history and much other vital information reflecting the timeline of various communities. Serving as an active agent of both information and entertainment at the community level for so many years today, there arises an immediate need to preserve this form of storytelling - Folktales, especially in the context of its presentation has witnessed a change in recent times. Animation being the latest medium of entertainment, folktales can also be narrated in the form of animation that will also help preserve the stories in animated form for future generations. By doing so, folktales can be pushed beyond the boundaries of the community level and can be prevailed in the global platform to benefit the entire human race. Several communities across the globe have converted their folktales into animated movies to acquire the wider reach of audiences globally. This also helps to popularize the old traditions of these communities so that the newer generations can understand its significance in the present-day context of digital platforms. Moreover, extinguishing the line of the geographical divide, it ties people living across the world together through its common thread of lesson learning folktales.